Fabrication luminescence and radiation shielding properties of Gd2O3–La2O3–ZnO–B2O3–Sm2O3 glasses. (January 2023) - Kaewjaeng, S.; Kothan, S.; Wantana, N.; Kim, H.J.; Rajaramakrishna, R.; Jumpee, C.; Limsuwan, P.; Kaewkhao, J.
Abstract: The purpose of developing high transparency radiation shielding materials and luminescence materials with stoichiometric ratio of x Gd2 O3 :10La2 O3 :10ZnO:(79- x ) B2 O3 : 1Sm2 O3 where x = 0, 5, 10, 15, and 20 mol% using melt quenching technique. The physio-optical properties such as molar volume, density, concentration of rare-earth ions, polaron radius, inter-ionic radius, optical basicity, average distance between rare-earth ions, and optical packing density of the present glasses has been evaluated. The glass samples obtained show high density which is vital factor for radiation shielding. The absorption spectra show significant of bands Sm 3+ ions. The FTIR results of Gd-La-Zn-B-Sm (Gd-1Sm) glass samples show signature borate BO3 and BO4 vibrational units in Gd-1Sm glass samples. The μ, μm, HVL, TVL, and MFP were evaluated and showed that the values decrease with increasing X-ray energy whereas increase with an increase in Gd2 O3 content suggesting their potential use in X-ray diagnosis regions. The HVL value was compared with commercial windows, concrete, Serpentine and X-ray windows and found that the glasses doped with 10 mol%, 15mol%, and 20 mol% Gd2 O3 content showed better results than X-Ray windows at 10 kVp. The emission and excitation spectra of glass samples were studied and emission spectra show orange emission bands. The experimental lifetime analysis shows that the glass samples show decreasing trend from 1.161 to 1.128 ms with an increase in Gd 3+ ions exhibiting single exponential nature. Highlights: Novel glass fabrication to enhance the radiation shielding and activate the luminescent center. HVL values were evaluated and found to be comparable with commercial window glasses. Energy transfer from Gd 3+ to Sm 3+ ions were observed. Bright reddish-orange emitting glasses when monitored under 365 nm UV lamp. Total integral scintillation efficiency was 38% compared to BGO crystal.